Twice in a blue moon - Lauren, Christina (Gallery Books, 2019)
From the New York Times bestselling author of The Unhoneymooners and the "delectable, moving" (Entertainment Weekly) My Favorite Half-Night Stand comes a modern love story about what happens when your first love reenters your life when you least expect it...